2021
DOI: 10.3389/fpsyg.2021.734106
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19, Telecommuting, and (Virtual) Sickness Presenteeism: Working From Home While Ill During a Pandemic

Abstract: This study explored (virtual) sickness presenteeism in the context of the COVID-19 pandemic. Using qualitative data from 505 members of the German working population, it investigates how working from home, which rapidly increased because of the COVID-19 outbreak, is perceived with regard to the pandemic. The study explored how this development affects the decision to show absence or presence in case of illness. More than 1,300 responses to different open-end questions by presenteeists and non-presenteeists wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 54 publications
1
22
0
Order By: Relevance
“…Previous studies have reported that workers who prefer telework choose teleworking when feeling unwell because this allows them to work at their own pace and freely adjust their break time. 26,27 Other previous studies state that female employees with children choose to telework but are not highly satisfied with telework. 28,29 Attention to the background related to teleworking preferences is important to support teleworkers with severe work functioning impairment.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies have reported that workers who prefer telework choose teleworking when feeling unwell because this allows them to work at their own pace and freely adjust their break time. 26,27 Other previous studies state that female employees with children choose to telework but are not highly satisfied with telework. 28,29 Attention to the background related to teleworking preferences is important to support teleworkers with severe work functioning impairment.…”
Section: Discussionmentioning
confidence: 97%
“…The preference for teleworking could be based on difficulties with working in the workplace owing to ill health or work–family conflicts. Previous studies have reported that workers who prefer telework choose teleworking when feeling unwell because this allows them to work at their own pace and freely adjust their break time 26,27 . Other previous studies state that female employees with children choose to telework but are not highly satisfied with telework 28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that workers who prefer telework choose teleworking when feeling unwell because this allows them to work at their own pace and freely adjust their break time. 26,27 Other previous studies state that female employees with children choose to telework but are not highly satisfied with telework. 28,29 Attention to the background related to teleworking preferences is important to support teleworkers with severe work functioning impairment.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, adequate internal (i.e., CSE) and external (i.e., job control) resources might help maintaining performance when health is impaired (Karanika-Murray & Biron, 2020 ). Currently, the influences of the COVID-19 pandemic on (virtual) sickness presenteeism while working from home are also being investigated (Ruhle & Schmoll, 2021 ). This needs further exploration.…”
Section: Discussionmentioning
confidence: 99%